Creep-recovery behaviors of articular cartilage under uniaxial and biaxial tensile loadings - Gao, Lilan; Liu, Gang; Tan, Yansong; Li, Ruixin; Zhang, Chunqiu; Gao, Hong; Zhao, Bingjie (Frontiers in Bioengineering and Biotechnology, 2023)
Creep deformation in cartilage can be observed under physiological loads in daily activities such as standing, single-leg lunge, the stance phase of gait. If not fully recovered in time, it may induce irreversible damage in cartilage and further lead to early osteoarthritis. In this study, 36 cruciform-shape samples in total from 18 bulls were employed to conduct the uniaxial and biaxial creep-recovery tests by using a biaxial cyclic testing system. Effects of stress level (0.5, 1.0, 1.5MPa) and biaxial stress ratio (0, 0.3, 0.5, 1.0) on creep-recovery behaviors of cartilage were characterized. And then, a viscoelastic constitutive model was employed to predict its creep-recovery behaviors. The results showed that the creep strain and its three components, namely instantaneous elastic strain, delayed elastic strain and viscous flow strain, increase with the increasing stress level or with the decreasing biaxial stress ratio. Compared with uniaxial creep-recovery, biaxial creep-recovery exhibits a smaller creep strain, a faster recovery rate of creep strain and a smaller residual strain. Besides, the built viscoelastic model can be used to describe the uniaxial creep-recovery behaviors of cartilage as a good correlation between the fitted results and test results is achieved. The findings are expected to provide new insights into understanding normal joint function and cartilage pathology.